2012
DOI: 10.1159/000342994
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Obesity

Abstract: Important interaction exists between thyroid function, weight control, and obesity. Several mechanisms seem to be involved, and in studies of groups of people the pattern of thyroid function tests depends on the balance of obesity and underlying thyroid disease in the cohort studied. Obese people with a normal thyroid gland tend to have activation of the hypothalamic-pituitary-thyroid axis with higher serum TSH and thyroid hormones in serum. On the other hand, small differences in thyroid function are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 75 publications
3
127
0
9
Order By: Relevance
“…Besides its influence on thermogenesis, T 3 might also influence REE by regulating the spontaneous motor activity. Indeed, shortly after the injection of T 3 into the pre-optic region of hypothyroid rats, an increase in motor activity is observed (16).…”
Section: The Thermogenic Effect Of Thyroid Hormonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides its influence on thermogenesis, T 3 might also influence REE by regulating the spontaneous motor activity. Indeed, shortly after the injection of T 3 into the pre-optic region of hypothyroid rats, an increase in motor activity is observed (16).…”
Section: The Thermogenic Effect Of Thyroid Hormonesmentioning
confidence: 99%
“…Body weight regulation is achieved through a finetuning between energy intake and energy consumption, the latter being determined by resting energy expenditure (REE), non-exercise activity, and voluntary physical activity. In homeothermic species, such as humans, T 3 has acquired a critical role in temperature homeostasis and is responsible for w30% of REE (11). The T 3 -induced thermogenic activity is exerted through the thyroid hormone receptor a (TRa) (12,13), while TRb is a key regulator of cholesterol metabolism (14).…”
Section: The Thermogenic Effect Of Thyroid Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…There also was a trend toward increased triglyceride concentration, consistent with the lipogenic pathway being activated functionally. Interestingly, a significant proportion of patients experience weight gain after successful therapy for hyperthyroidism (33). Although the precise mechanism(s) for this observation is not known, it has been suggested that a delayed adaptation of appetite and food intake in combination with the decreased energy expenditure after returning to euthyroidism may be contributory (34).…”
Section: Adaptations During Hyperthyroidism and Withdrawal 857mentioning
confidence: 99%
“…The association between obesity and thyroid function is complex, because overeating with accumulation of fat and the development of obesity seems to activate the hypothalamic-pituitary-thyroid axis, leading to changes in thyroid function tests, which overlap with abnormalities seen in primary thyroid disease [5].…”
Section: Introductionmentioning
confidence: 99%